Analisis Kelayakan Pengembangan Proyek Apartemen Citra Living Citra Garden City - Citra Sari Kusuma Wardhani dan Yanuar (Universitas Tarumanagara, 2019)
Jakarta is experiencing a favourite residential growth due to the high level of urban migration to Indonesia’s capital. Therefore, PT CD, through its subsidiary, PT CMG, KSO, tries to fulfill the increasing demand of residential housing by developing a ± 1 ha of land in the West of Jakarta. The development is called the Apartement Citra Living project. This paper is developed to determine the feasibility of the project through cash flow sensitivity analysis. There are 2 (two) assumptions used, which are : the normal, and optimistic assumptions. These assumptions are tested through 4 (four) calculation methods: Payback Period, Net Present Value (NPV), Internal Rate of Return (IRR) and Profitability Index (PI). The results of the sensitivity analysis are as follows Payback periods for the project are 8 months for normal and, 3 months for optimistic; The NPV is positive for all assumptions; The IRR for the normal and optimistic assumptions are higher than the Weighted Average Cost of Capital (WACC) 10%. The PI for normal and optimistic assumptions are more than 1 (one). So, the project is feasible. Therefore, based on the results of the sensitivity analysis of the project’s cash flow, it is concluded that the Apartement Citra Living project is a profitable business decision. To increase profitability level, the company should try to find other financing alternatives to lower the cost of capital.